Effectiveness of Strawberry Extract with 100% Concentration in Cleaning Teeth with Extrinsic Stain at the Academic Community of Poltekkes Kemenkes Jakarta I - Ita Astit Karmawati; Ita Yulita; Rahaju Budiarti; Syifa Yulia Lestari (Health Notions, 2020)
Discoloration of teeth can be caused by stains on the surface of the teeth or due to changes in tooth material. Tooth stain can be extrinsic, intrinsic, or age-related. Tooth whitening (bleaching) can be done in the office and at home. Strawberry is a fruit with many benefits, one of which is whitening teeth. The content of malic acid and ellagic acid in strawberries has the effect of tooth whitening. The purpose of this study was to determine the effectiveness of strawberry extract with a concentration of 100% in cleaning teeth with the extrinsic stain on an academic member of the Health Polytechnic Jakarta I. This study was an experiment on 31 people who had upper and lower anterior teeth with the extrinsic stain as samples. Data collection was done by applying strawberry extract with a concentration of 100% on the surface of the anterior teeth, allowed to stand for 5 minutes, then brushed and rinsed with water. This procedure was done 2 times a day for 5 consecutive days. Changes in extrinsic stain were measured using the Lobene Stain Index which measures the intensity and area of the stain, as well as a combined score of both. The average combined score with measurements using the Lobene Stain Index for extrinsic stain before being treated with strawberries was 22.4. The score has decreased every day starting from day 1 to day 5 of treatment. The largest decrease of the average Combined Score was occurred on the 2nd day, namely from a score of 20.0 on the 1st day to 14.6 on the 2nd day with a percentage reduction of 35.0%. Statistical tests showed significant results of 0,000 reducing the Intensity Score and Area Score on day 2 to day 5. It can be concluded that there was a significant decrease in extrinsic stain scores after treatment on day 2. Keywords: extrinsic stain; strawberry extract